2010
DOI: 10.1029/2009gl041320
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol climate feedback due to decadal increases in Southern Hemisphere wind speeds

Abstract: [1] Observations indicate that the westerly jet in the Southern Hemisphere troposphere is accelerating. Using a global aerosol model we estimate that the increase in wind speed of 0.45 ± 0.2 m s À1 decade À1 at 50-65°S since the early 1980s caused a higher sea spray flux, resulting in an increase of cloud condensation nucleus concentrations of more than 85% in some regions, and of 22% on average between 50 and 65°S. These fractional increases are similar in magnitude to the decreases over many northern hemisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 26 publications
6
83
0
Order By: Relevance
“…This causes a sizable increase in sea-salt concentration in these areas (75% and 51% increases in sea-salt burdens poleward 60 • N and 60 • S, respectively) in response to a doubling of CO 2 . Given that sea salt particles comprise a significant fraction of CCN concentrations in these regions (e.g., Spracklen et al, 2005), such large changes are likely to cause a large forcing through changes in cloud drop number (Korhonen et al, 2010).…”
Section: Sea Salt Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…This causes a sizable increase in sea-salt concentration in these areas (75% and 51% increases in sea-salt burdens poleward 60 • N and 60 • S, respectively) in response to a doubling of CO 2 . Given that sea salt particles comprise a significant fraction of CCN concentrations in these regions (e.g., Spracklen et al, 2005), such large changes are likely to cause a large forcing through changes in cloud drop number (Korhonen et al, 2010).…”
Section: Sea Salt Particlesmentioning
confidence: 99%
“…Thus the first major challenge is to demonstrate the explanatory power of complex chemical schemes against observations and the second challenge is to develop accurate simpler schemes that are fast enough to run on centennial timescales. Many global models now include microphysical schemes sufficient to simulate the response of CCN to changes in DMS and sea spray (e.g., Korhonen et al, 2008Korhonen et al, , 2010Kloster et al, 2008;Woodhouse et al, 2010), and these models are suitable for inclusion in Earth system models. A major challenge is to evaluate these aerosol models against observations of DMS and CCN on seasonal and interannual timescales in different regions.…”
Section: Summary and Status Of Marine Aerosol In Earth System Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentener et al, 1996;Hoyle et al, 2011). Second of all, natural aerosol particles are part of various climate feedback loops, as their future concentration levels are expected to change with changing climate conditions (Arneth et al, 2010;Carslaw et al, 2010;Korhonen et al, 2010;Quinn and Bates, 2011;Kulmala et al, 2004Kulmala et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…A strengthening and poleward shift of the westerly windsas has been driven by stratospheric ozone depletion 15 -may also act to cool the region south of the ACC via enhanced Ekman advection of cold surface waters northward [15][16][17] . Moreover, strengthened surface winds may increase low cloud reflectivity via enhanced emissions of sea spray, and it has been proposed that this effect -together with the direct radiative forcing of stratospheric ozone depletion -has more than offset greenhouse gas (GHG) forcing south of the ACC since the 1980s 18 . Additionally, it has been suggested that the extensive SO sea-ice cover itself may slow the rate of warming by shielding the sea surface from radiative forcing 19 .…”
mentioning
confidence: 99%